INOVASI PENDIDIKAN ANAK USIA DINI DI INDONESIA ERA GLOBALISASI - SANTOSO, SOEGENG (PPs UNJ, 2011)
Many theories or concepts Early Childhood Education (ECD) of the various countries, this time put forward the concept of early childhood education in Indonesia is animated by the idea created by Ki Hajar Dewantara, Founder of University Park students. Actually, the concept of Ki Hajar Dewantara pads principle that a combination of theory Froebel (German) and Montessori (Italy) adjusted to the Indonesian culture. Indonesian culture is very broad and complex to be developed and preserved. In addition there are other universities that INS jugs (Indonesische National School) Kayutanam in West Sumatra led by Mohammad Sjafei, Muhammadiyah in Yogyakarta led KH Moh. Dahlan, Boarding Schools in some areas and the Peoples University in Jakarta, but not much to talk about early childhood education.Keywords: innovation, globalization, early childhood